Cr2AlC MAX phase as bond coat for thermal barrier coatings: Processing, testing under thermal gradient loading, and future challenges. Issue 4 (11th December 2019) - Gonzalez‐Julian, Jesus; Mauer, Georg; Sebold, Doris; Mack, Daniel E.; Vassen, Robert
Abstract: Cr2 AlC layers with thickness up to 100 µm were deposited by high‐velocity‐atmospheric plasma spray (HV‐APS) on Inconel 738 substrates to analyze the potential of MAX phases as bond coat in thermal barrier coating systems (TBCs). The deposited Cr2 AlC layers showed high purity with theoretical densities up to 93%, although some secondary phases were detected after the deposition process. On top of this MAX phase layer, a porous yttria‐stabilized zirconia (YSZ) was deposited by atmospheric plasma spraying. The system was tested under realistic thermal loading conditions using a burner rig facility, achieving surface and substrate temperatures of 1400°C and 1050°C, respectively. The system failed after 745 cycles mainly for three reasons: (i) open porosity of the bond coat layer, (ii) oxidation of secondary phases, and (iii) inter‐diffusion. Nevertheless, these results show a high potential of Cr2 AlC and other Al‐based MAX phases as bond coat material for high‐temperature applications. Furthermore, future challenges to transfer MAX phases as eventual bond coat or protective layer are discussed.